2023
DOI: 10.1021/acs.iecr.3c01170
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Light Trapping and Water Management in Interconnected Porous PEDOT:PSS Hydrogels for Efficient Solar-Driven Water Purification

Abstract: Interfacial solar water purification is emerging as a sustainable and environmental-friendly approach for solar energy harvesting and clean water production. Currently, the limited photothermal conversion efficiency restricts its practical applications. Developing evaporators with porous structures has been proposed as a promising way toward boosting solar-thermal-vapor conversion by enhancing energy utilization and evaporation area. However, effective collaboration between light capture and water management o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 60 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…In conjunction with the conclusion in Section , excessive formation of PEDOT occurs within the composite sponge-like hydrogel when the polymerization time is excessively long, rendering these PEDOT particles ineffective for photothermal conversion. Additionally, due to PEDOT’s hydrophobic nature, it reduces water transfer efficiency within the composite sponge-like hydrogel and subsequently affects its water evaporation rate. , Further extending the polymerization time to 12 and 24 h, it can be found that the water evaporation rate drops further to 2.37 and 2.03 kg/m 2 h. Meanwhile, high light intensity prompts steam generation for SPH-6, as shown in Figure S7. The evaporation rates reached 3.76 and 4.58 kg/m 2 h under 1.5 and 2 sun illumination, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…In conjunction with the conclusion in Section , excessive formation of PEDOT occurs within the composite sponge-like hydrogel when the polymerization time is excessively long, rendering these PEDOT particles ineffective for photothermal conversion. Additionally, due to PEDOT’s hydrophobic nature, it reduces water transfer efficiency within the composite sponge-like hydrogel and subsequently affects its water evaporation rate. , Further extending the polymerization time to 12 and 24 h, it can be found that the water evaporation rate drops further to 2.37 and 2.03 kg/m 2 h. Meanwhile, high light intensity prompts steam generation for SPH-6, as shown in Figure S7. The evaporation rates reached 3.76 and 4.58 kg/m 2 h under 1.5 and 2 sun illumination, respectively .…”
Section: Resultsmentioning
confidence: 99%